Extranodal B Cell Lymphoma in the Trachea of a Domestic Cat - Jardim, Mariana Palha de Brito; Cid, Gabriela de Carvalho; Meirelles, Ana Carolina Azevedo; Damico, Cristiane Brandão; Nogueira, Vivian de Assunção; Moreira de Souza, Heloisa Justen (Acta Scientiae Veterinariae, 2020)
Background: Primary tracheal tumors are considered uncommon in veterinary medicine and among them extranodal tracheal lymphoma, which is a neoplastic type, has rarely been described, especially with the use of immunophenotyping. Consequently, there is a lack of knowledge inherent to the characteristics of this tumor type in felines and as a result little information on how to deal with animals affected by this disease. Therefore, there is a need for more studies focusing on this matter. The objective of this work is to report a case of extranodal B cell lymphoma in the trachea of a domestic cat and point out the clinical and pathological characteristics of this neoplastic type. Case: A 5-year-old domestic cat, of an oriental breed, was taken to a veterinary clinic exclusively for cats in Rio de Janeiro, Brazil. The main complaint was difficulty in breathing and loss of appetite and historical data included intolerance to exercise. A clinical examination confirmed inspiratory dyspnea and upper respiratory sounds. Hematological and serum biochemical exams did not evidence any noteworthy changes and the cat was considered negative for feline viral leukemia and feline immunodeficiency viruses through serological and molecular testing. However, in the radiographic examination of the thoracic cervical region, an opacity was observed that occluded part of the tracheal lumen and this was suggestive of a mass in the initial third of the trachea, measuring 0.5 cm in diameter. The animal was stabilized and then 24 h after admission underwent inspection of the oral cavity and a biopsy of the tracheal mass was performed. Cytology of the specimen was suggestive of lymphoma. The treatment of choice was: lomustine with a single, oral dose of 10 mg; vincristine sulfate with a single intravenous dose of 0.75 mg/m²; and methylprednisolone acetate with a single intramuscular dose of 20 mg. A second radiograph taken 24 h after the chemotherapy showed that the tracheal mass had shrunk to 0.3 cm in diameter. Seven days after the treatment adopted for lymphoma, the mass was no longer visible. Histopathological analysis and immunohistochemistry supported the diagnosis of B cell lymphoma. A 36-month follow-up after the initial admission showed that the cat was in good health, without any respiratory signs and/or alterations in imaging tests that could suggest neoplastic recurrence. Discussion: The majority of animals with tracheal lymphoma are more than seven years old; thus, this report is one of the few that describes this tumor type in a young cat, and therefore highlights the importance of considering tracheal lymphoma as a differential diagnosis in young cats with clinical findings compatible with this condition. The successful treatment carried out here was attributed to the immunophenotyping of the neoplasia, because when B cell trachea lymphoma is diagnosed early and correctly there is usually a good prognosis. Type T lymphomas exhibit a poorer clinical response through therapy than B cell lymphomas. As far as the authors know, this is only the fifth report in which immunophenotyping of a tracheal lymphoma in a cat has been performed. The relevance of studies involving the immunohistochemistry of this tumor type in cats is asserted, so that the differentiation between B or T cell lymphomas can provide greater accuracy in dealing with animals affected with this disease.